(untitled) (Journal of the College of Basic Education, 2022)
Pitt is one of the most famous Irish leaders of the nineteenth century and was the first to make the term "home rule" an effective political slogan, and he was the first to found the Home Government League and was its first president.The research consisted of an introduction, two chapters and a conclusionThe first topic dealt with Bitt’s life and his studies until he entered the world of politics in 1852. The topic focused on Bitt’s parliamentary life and his role in establishing the Self-Government League in 1870.